Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1093/jpepsy/jsx057
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Primary Medical-Behavioral Health Care for Adolescent and Young Adult Depression: Predictors of Service Use in the Youth Partners in Care Trial

Abstract: Results support the value of integrated medical-behavioral health care for improving rates of care. Findings highlight mechanisms by which integrated care may lead to improved rates of care and outcomes for AYA, an underserved and understudied group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 73 publications
0
39
0
Order By: Relevance
“…Two studies (Kozlowski et al, 2015;Richardson et al, 2009) reported results from a small, single-arm pilot study. Six studies (Kolko et al, 2014;Kolko et al, 2010;Kolko et al, 2012;Yu et al, 2017;Richardson et al, 2014;Wright et al, 2016;Rapp et al, 2017;Asarnow et al, 2005;Asarnow et al, 2009) reported implementation outcomes from randomized controlled trials (RCTs) of co-located interventions for mental health problems, although none of these randomized by implementation strategy. The remaining 7 studies (Hine et al, 2017;Levy et al, 2017;Horwitz et al, 2016;Rousseau et al, 2017;Aguirre & Carrion, 2013;Westerlund et al, 2017;Riley et al 2018) reported results from surveys or interviews with providers from pediatric practices that had implemented co-located behavioral health care.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies (Kozlowski et al, 2015;Richardson et al, 2009) reported results from a small, single-arm pilot study. Six studies (Kolko et al, 2014;Kolko et al, 2010;Kolko et al, 2012;Yu et al, 2017;Richardson et al, 2014;Wright et al, 2016;Rapp et al, 2017;Asarnow et al, 2005;Asarnow et al, 2009) reported implementation outcomes from randomized controlled trials (RCTs) of co-located interventions for mental health problems, although none of these randomized by implementation strategy. The remaining 7 studies (Hine et al, 2017;Levy et al, 2017;Horwitz et al, 2016;Rousseau et al, 2017;Aguirre & Carrion, 2013;Westerlund et al, 2017;Riley et al 2018) reported results from surveys or interviews with providers from pediatric practices that had implemented co-located behavioral health care.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
“…Other observational studies were inclusive of all children within the target population (which at times was age-restricted) identified as needing mental health support. Contrasting with the observational studies, all six RCTs studied disorder or symptom-specific interventions within a targeted age range, including three for school-age children with disruptive behavior (Kolko et al, 2014;Kolko et al, 2010;Kolko et al, 2012) (two of which reported on studies using the same intervention), and three for adolescents with depression (Mufson et al, 2018;Richardson et al, 2014;Wright et al, 2016;Rapp et al, 2017;Asarnow et al, 2005;2009). Table 3 includes a list of implementation outcomes highlighted in each study, along with highlighted results, limitations, and "main lessons" on implementation based on our discussions.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis on depression treatment in pediatric populations found small yet significant effects for primary care-based integrated care, with the strongest evidence found for collaborative care [ 68 ]. Adolescents enrolled in collaborative care programs have shown increased engagement in active treatment despite initial hesitation compared to those receiving treatment as usual [ 69 ]. Observational studies from our PCMH at the Mayo Clinic found that pediatric patients enrolled in collaborative care reported higher depression response and remission rates than patients receiving usual care [ 70 •].…”
Section: Special Considerations For Treating Depression In the Pcmh: mentioning
confidence: 99%
“…2013). Thus, this approach allows increased access to services (Goodwin et al, 2017), lower redundancies in care (Rapp et al, 2017), and improved professional collaboration (Aitken & Curtis, 2004), all of which may enhance client outcomes and lower health care costs (Berwick et al, 2008;Kwan & Nease, 2013;Rapp et al, 2017).…”
mentioning
confidence: 99%